The extent to which Palestinian audit offices comply with the requirements of the International Standard for Quality Management (ISQM 1) - Siaj, Etedal Robeen (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to identify the extent of the commitment of audit offices in Palestine to the elements of quality management contained in the International Standard for Quality Management ISQM1, in addition to identifying the differences in the commitment of audit offices in Palestine to the elements of quality management contained in the International Standard for Quality Management ISQM1 according to the variables Demographics, To achieve these goals, the researcher followed the descriptive analytical approach, and the study population consisted of (260) auditing offices according to (the Palestinian Auditor’s Guide 2024), and a random sample was taken from them, which represented (63) offices, and the questionnaire was used as a tool for collecting information, and from The most important findings of the study are that there is a high commitment by audit offices in Palestine to the elements of quality management contained in the International Standard for Quality Management ISQM1, In addition, there are no statistically significant differences in the commitment of audit offices in Palestine to the elements of quality management according to the variables Demographics, Among the most important recommendations that the study recommends is increasing the interest of other parties in understanding and fulfilling the relevant behavioral requirements to which the audit office is subject, in addition to the need for the audit office to investigate completed engagements, and the importance of evaluating Quality management systems at least annually.